Civil Sphere untuk Harmoni Sosial Islam-Kristen di Desa Inklusi Bah Sulung Sumatera Utara - Sihombing, Helpin Maryand; Tampake, Tony; Lattu, Izak (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This article aims to argue about the Inclusion Village Program as a shared space or civil sphere in Bah Sulung Village, with the aim of building social harmony between religious communities. The main focus of this problem is the lack of involvement and acceptance between religious communities in the Bah Sulung community. The Inclusion Village Program was held as an effort to accommodate diversity and build harmonious social relations. In analyzing this research, Jefri Alexander's thinking, namely the civil sphere, is used as a scalpel for analyzing this research. This research uses a qualitative research method with a realist ethnographic approach, involving structured interview techniques with key informants, observations in Bah Sulung village and literature study. The research results show that interactions between religious communities appear in daily life relationships and in the customary system also play a role in creating social solidarity through the Inclusive Village program. In conclusion, the Bah Sulung community has the potential to build a social life of solidarity and harmony